Improved Stability and Performance of Surface Acoustic Wave Nanosensors Using a Digital Temperature Compensation - Balashov, S. M.; Rocha, J. M.; Hurtado, M. R. F.; Prestes, J. A. L.; de Campos, A. F. M; Moshkalev, S. A. (Frontiers in Sensors, 2021)
Surface Acoustic Waves (SAW) sensors are known to be an excellent choice for a measurement of a small amount of analyte in gas mixtures. The use of this type of sensors is limited until now in the industrial environment due to the dependence of its response to temperature variations. To overcome this problem normally thermal stabilization of equipment is used. We propose here a simple procedure of compensation of thermal drift in SAW sensors, allowing to perform measurements in temperature intervals of up to 20 degrees without any thermal stabilization of the sensitive element of a sensor. By monitoring the temperature of the key point of the sensor and applying the proposed polynomial compensation it is possible to reduce the influence of thermal instabilities of the ambient to the response more than four times. The method is illustrated by a temperature compensated SAW humidity sensor with graphene oxide nanofilms as water sensitive elements. The results show enhanced performance of the sensor in a large temperature interval.